2015
DOI: 10.1038/npjamd.2015.9
|View full text |Cite
|
Sign up to set email alerts
|

Role of the central nervous system and adipose tissue BDNF/TrkB axes in metabolic regulation

Abstract: Background/Objectives:Brain-derived neurotrophic factor (BDNF) and its receptor (tropomyosin-related kinase B: TrkB, also known as Ntrk2) have a key role in central regulation of the energy balance. BDNF and TrkB are also expressed in the peripheral tissues, including adipose tissue, but their peripheral role has been unclear. Here we report on the functional significance of the adipose tissue BDNF/TrkB axis in metabolic homeostasis.Materials and Methods:To examine the role of the BDNF/TrkB axis in the central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 53 publications
7
52
0
Order By: Relevance
“…Using instead an adipoqcre (mature adipocyte-speci c line) there was no obesity in a BDNF or a TrkB knock-out (KO), and the BDNF KO showed no difference in adipose BDNF levels (28). Together, these ndings suggested that mature adipocytes are not the cellular source of BDNF (28), which we have con rmed in this study by demonstrating predominance of BDNF expression in the SVF. NFs are secreted by glial cells in the brain (29) and Schwann cells in peripheral tissues (30).…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Using instead an adipoqcre (mature adipocyte-speci c line) there was no obesity in a BDNF or a TrkB knock-out (KO), and the BDNF KO showed no difference in adipose BDNF levels (28). Together, these ndings suggested that mature adipocytes are not the cellular source of BDNF (28), which we have con rmed in this study by demonstrating predominance of BDNF expression in the SVF. NFs are secreted by glial cells in the brain (29) and Schwann cells in peripheral tissues (30).…”
Section: Introductionsupporting
confidence: 71%
“…A few studies have clearly shown that NFs, including BDNF, are present in adipose tissue (25)(26)(27), but the cellular source of BDNF in adipose had not been determined. In adipose speci c (FABP4-Cre) knock-outs of BDNF or TrkB, only CNS effects were apparent (not surprising given off-target brain effects of this cre line) (28). Using instead an adipoqcre (mature adipocyte-speci c line) there was no obesity in a BDNF or a TrkB knock-out (KO), and the BDNF KO showed no difference in adipose BDNF levels (28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cells have been shown to express BDNF, including: platelets [Yamamoto and Gurney, 1990], developing heart [Clegg et al, 1989], vascular smooth muscle cells [Clegg et al, 1989], developing intestine [Clegg et al, 1989], spleen [Yamamoto et al, 1996], T-cells, B-cells, monocytes [Kerschensteiner et al, 1999;Nakahashi et al, 2000], and skeletal muscles [Mousavi and Jasmin, 2006]. In addition, the BDNF mRNA has been detected in several tissues such as the colon, leukocytes, ovary, spleen, thymus, testis, pancreas as well as in blood Pruunsild et al, 2007;Nakagomi et al, 2015]. Interestingly, altered BDNF expression occurs in response to some events in an activity-dependent manner.…”
Section: Regulation Of Bdnf Expressionmentioning
confidence: 99%
“…A few studies have clearly shown that NFs, including BDNF, are present in adipose tissue (25)(26)(27), but the cellular source of BDNF in adipose had not been determined. In adipose specific (FABP4-Cre) knock-outs of BDNF or TrkB, only CNS effects were apparent (not surprising given off-target brain effects of this cre line) (28).…”
Section: Introductionmentioning
confidence: 99%